Efektivitas Penggunaan Stik Ajaib Dalam Meningkatkan Pemahaman Operasi Hitung Pada Siswa SD - Selviana, Helvi Rinanda; Minsih, Minsih (Graduate School of Universitas Negeri Malang, 2024)
Learning media is a tool that can be used to convey or transmit messages from the sender to the receiver. Concrete learning media, such as math manipulatives, are tools that allow students to learn concretely through the use of physical objects that they can hold, see, and utilize in the learning process so that students are not easily bored during the learning process. The use of concrete learning media can provide motivation to students during the learning process. The purpose of this study was to determine the effectiveness of using magic sticks in improving the understanding of counting operations in grade 2 elementary school students. The type of research used was a pseudo experiment. The population of this study was class II which amounted to 27 students. The sampling technique used saturated sampling which uses all members of the population as samples. Data were collected through the implementation of pretest and posttest tests. The validity of the instrument was measured using validity and reliability. With data analysis using normality test, homogeneity test and T test. The results showed an increase in grades after using magic stick media on grade II students of SD Negeri 1 Sukorame. The hypothesis proposed has been accepted based on the results of the T test which shows the t value of 5.669 is greater than the t table value of 2.056. It is proven that the use of magic sticks in the math learning process can improve student learning outcomes at SD Negeri 1 Sukorame.